Effective properties of 0–3, 1–3, and 2–2 composites based on unified unit-cell micromechanics model. (January 2022) - Lin, Chien-hong
Highlights: We present a unified unit-cell micromechanics model to predict the effective elastic constants for two-phase composites. A novel unit cell that employs the minimum number of subcells to concurrently modeling 0–3, 1–3 and 2–2 composites is developed. The presented model retains explicit predictions for effective properties. The predictions of the presented model are close to those from the mori-tanaka model. Abstract: This paper presents a micromechanics method, dubbed unified unit-cell model, to predict the effective elastic constants of 0–3, 1–3, and 2–2 composites. Considering periodic composites, a representative volume element can be identified as a unit cell which is further uniquely divided into only four subcells. This novel configuration of a unit cell achieves concurrently modeling of 0–3, 1–3 and 2–2 composites by employing the minimum number of subcells, in comparison with existing unit cell-based micromechanics models. Effective properties are formulated by the use of concentration-factor tensors that are determined via the micromechanical relations based on the continuity conditions among the unit cell and its subcells. The presented formulation retains explicit predictions for the effective properties. Numerical results for particulate, fibrous, and laminated composites are presented to demonstrate the comparability of the presented model with the Mori-Tanaka model, and the models are compared in light of existing experimental data of 0–3 composites.